Dissonance Between Internal Migration and Citizenship Rights in Nepal - Thapa, Binayak Krishna; Sharma, Sagar Raj (Bodhi: An Interdisciplinary Journal, 2023)
This paper discusses the issues pertaining to internal migration and citizenship regulations for people in Nepal, especially those concerning the vital registration rights of the citizens and their free movement across administrative boundaries. The data for this purpose is based on field work conducted in the district headquarters of Bhojpur in Eastern Nepal, where temporary migrants that had come from remote villages were interviewed. The authors delves into exploring how temporary migrants are facing exclusion from membership to self-help group and user committees which islooked upon as lack of citizenship rights conferred to them by the state. It is seen that free mobility does not always amount to extension and enhancement of citizenship rights, and, through the practice of free movement, migrants without migration registrations have been getting lesser access to social rights and civil and political entitlements.